2018
DOI: 10.1002/ccr3.1440
|View full text |Cite
|
Sign up to set email alerts
|

A case report of hypersomnia in tetrasomy X improved with medical therapy

Abstract: Key Clinical MessageTetrasomy X is a rare chromosomal anomaly in which sleep disorders have not been previously reported. We report on one patient with tetrasomy X and hypersomnia successfully treated with psychostimulant therapy. Sleep disorders are rarely reported in chromosomal anomalies. Clinicians should screen patients for sleep disorders and manage them appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Among all these mosaicisms, only one fetus have 48,XXXX mosaicism karyotype. It was reported that girls with tetrasomy X had dysmorphic facial features, varying degrees of cognitive dysfunction, speech and language disorders and skeletal and connective tissue disorders 17 . There are sex chromosomal or autosomal structure abnormality for 6 cases, including inversion, translocation, isochromosome, dicentric X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Among all these mosaicisms, only one fetus have 48,XXXX mosaicism karyotype. It was reported that girls with tetrasomy X had dysmorphic facial features, varying degrees of cognitive dysfunction, speech and language disorders and skeletal and connective tissue disorders 17 . There are sex chromosomal or autosomal structure abnormality for 6 cases, including inversion, translocation, isochromosome, dicentric X chromosome.…”
Section: Discussionmentioning
confidence: 99%